Long-distance delivery of bacterial virulence factors by Pseudomonas aeruginosa outer membrane vesicles. - Jennifer M Bomberger (Public Library of Science (PLoS), 2009)
Bacteria use a variety of secreted virulence factors to manipulate host cells, thereby causing significant morbidity and mortality. We report a mechanism for the long-distance delivery of multiple bacterial virulence factors, simultaneously and directly into the host cell cytoplasm, thus obviating the need for direct interaction of the pathogen with the host cell to cause cytotoxicity. We show that outer membrane-derived vesicles (OMV) secreted by the opportunistic human pathogen Pseudomonas aeruginosa deliver multiple virulence factors, including beta-lactamase, alkaline phosphatase, hemolytic phospholipase C, and Cif, directly into the host cytoplasm via fusion of OMV with lipid rafts in the host plasma membrane. These virulence factors enter the cytoplasm of the host cell via N-WASP-mediated actin trafficking, where they rapidly distribute to specific subcellular locations to affect host cell biology. We propose that secreted virulence factors are not released individually as naked proteins into the surrounding milieu where they may randomly contact the surface of the host cell, but instead bacterial derived OMV deliver multiple virulence factors simultaneously and directly into the host cell cytoplasm in a coordinated manner.